2020
DOI: 10.1007/s43076-020-00029-z
|View full text |Cite
|
Sign up to set email alerts
|

The Nencki Affective Picture System (NAPS): a Children-Rated Subset

Abstract: Emotion research in children should make use of emotional stimuli ideally coming from children-rated databases. However, most of the works in this area use adult-rated stimuli databases or a collection of stimuli taken from the Internet or from unidentified sources without any standardization procedure or content control for children population. These issues result in an overall lack of control over the kind of emotion to be elicited, leading to limited results. Therefore, in this work, a children-rated pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
5
2
Order By: Relevance
“…Our results extending this period of age. On contrary to Zamora et al (2020) and Cordon et al (2013) studies which did not report age-related differences, our study suggests a development of emotional valence discrimination also for pictures. In addition, our results indicated that emotional valence discrimination is modulated by the modality of the stimulus (i.e., words or pictures) and the kind of emotional valence to process (i.e., negative or neutral or positive).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results extending this period of age. On contrary to Zamora et al (2020) and Cordon et al (2013) studies which did not report age-related differences, our study suggests a development of emotional valence discrimination also for pictures. In addition, our results indicated that emotional valence discrimination is modulated by the modality of the stimulus (i.e., words or pictures) and the kind of emotional valence to process (i.e., negative or neutral or positive).…”
Section: Discussioncontrasting
confidence: 99%
“…For pictures, three studies investigated age or sex differences on children's emotional ratings. For age, Zamora, et al (2020) did not observed significant age-related differences in valence ratings between 8-to 10-year-old children and 10-to12-year-old ones. McManis et al (2001), observed that children (7-to 11-year-old) and teenagers (12-to 14-year-old) showed similar valence ratings of pictures than adults did.…”
Section: Introductioncontrasting
confidence: 58%
“…All the stimuli used in the tasks are from the NAPS, although for copyright reasons others were given as an example in the tasks. Prior to using the pictures with the sample of children, we rated the pictures for valence and arousal by testing Argentinian children of the same age groups on a 5-point (1–5) Likert scale (Zamora et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Children-Rated Subset is the most recent extension of NAPS and includes 1128 images from the original database that were rated as appropriate for children based on various criteria and expert judgment. In the Children-Rated Subset, affective ratings were collected from a sample of N = 266 children aged 8-12 years [44].…”
Section: The Naps and Naps Be Affective Picture Databasesmentioning
confidence: 99%